Chemically Modified Chitosan Supports for Phosphine-free Pd-catalyzed Crosscoupling Reaction of Arylboronic Acids with Acid Chlorides - Kong, Hyoung-Jun; Bang, Do-Won; Kim, Minji; Park, Soo-Youl; Kim, Seung-Hoi (Current Organic Chemistry, 2022)
Background: Phosphine-free Pd-catalytic platforms, i) combination with chitosan- Schiff base (CS-Py/Pd), ii) immobilized on chitosan-Schiff base (CS-Py@Pd), and iii) anchored to modified carbon nanotube support (CNT@CS-Py@Pd), Methods: They were evaluated regarding a novel pathway for the cross-coupling reaction of arylboronic acids with acid chlorides. Results: The CS-Py@Pd platform had the highest catalytic efficiency of the three platforms, yielding moderate to excellent yields of diaryl ketones. Conclusion: The catalytic activity of the Pd-catalyst was highly dependent upon the manufacturing process and type of support.
Keywords: Chitosan-Schiff base@Pd